The Effect of Self-Efficacy on Organizational Citizenship Behavior (OCB) of Science Teacher Candidates in Technology-Based Learning - Bahtiar Bahtiar (Postgraduate, University of Mataram, 2023)
The 21st century requires science teacher candidates to be skilled in using technology in learning. Science teacher candidate who is carrying out field practice experiences by applying technology-based learning must also have high self-efficacy and OCB. This study aimed to analyze self-efficacy's effect on the Organizational Citizenship Behavior (OCB) of science teacher candidates in technology-based learning. This research was conducted among the candidate of science teachers at Mataram Universitas Islam Negeri Mataram as many as 78 science teachers. The sampling technique used is probability sampling. The data collection used is the distribution of self-efficacy and OCB questionnaires. Data analysis used descriptive and inferential statistics in simple linear regression tests in the form of t-tests and significance. To measure self-efficacy using indicators of magnitude, generality, and strength, while to measure Organizational Citizenship Behavior using indicators of Altruism, Conscientiousness, Sportsmanship, Courtesy, and Civic Virtue. The results showed that the t-count value of 6.284 was greater than the t-table of 1.665. The significance value also shows 0.03. This shows that the significance value is smaller than the value of 0.05. The results of the hypothesis test indicate that the self-efficacy of science teacher candidates has a significant effect on Organizational Citizenship Behavior in technology-based learning